State Hegemony In Global Civil Society: The Articulation Of Indonesia's Ecpat Hegemony In The Process Of Securitization Of Child Sexual Exploitation - Oddie Bagus Saputra; Kevin Ali Sesarianto; Cindy Angie Octaviana; Zelda Mafaza R (Riviera Publishing, 2024)
The process of securitization of anti-child sexual exploitation norms (anti-ESA) carried out by ECPAT Indonesia relies on two hegemonic discourses, namely the global hegemonic discourse on children's rights and the political discourse on state hegemony. Looking at using the Securitization Theory, this study finds that ECPAT Indonesia disseminates the ESA threat to the local community as a securitization audience but without conducting equivalent socialization. This inequality arises due to the securitization model carried out by ECPAT Indonesia which is imposing through state hegemony instead of accommodating differences in norm structures between global and local communities. This argument is supported by using critical discourse analysis that looks at interviews with ECPAT Indonesia and the press releases they issue. In researching this issue, this study finds that ECPAT Indonesia does design their operations by utilizing the two hegemonies that have been mentioned.